Italian for beginner Polish university students: interference from L1 and LS - Favata, Giovanni (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
This paper aims to investigate the role of the individual linguistic repertoire in Italian language learning. We will conduct our analysis through the written productions of Polish students whilst learning Italian at the Italian as a second language classes organised by the University.